Ethnic differences in anthropometric measures and abdominal fat distribution: a cross-sectional pooled study in Inuit, Africans and Europeans. Issue 6 (13th January 2017) - Rønn, Pernille F; Andersen, Gregers S; Lauritzen, Torsten; Christensen, Dirk L; Aadahl, Mette; Carstensen, Bendix; Jørgensen, Marit E
Abstract : Background: Ethnic variation in abdominal fat distribution may explain differences in cardiometabolic risk between populations. However, the ability of anthropometric measures to quantify abdominal fat is not clearly understood across ethnic groups. The aim of this study was to investigate the associations between anthropometric measures and visceral (VAT) and subcutaneous abdominal adipose tissue (SAT) in Inuit, Africans and Europeans. Methods: We combined cross-sectional data from 3 studies conducted in Greenland, Kenya and Denmark using similar methodology. A total of 5275 individuals (3083 Inuit, 1397 Africans and 795 Europeans) aged 17–95 years with measures of anthropometry and ultrasonography of abdominal fat were included in the study. Multiple regression models with fractional polynomials were used to analyse VAT and SAT as functions of body mass index (BMI), waist circumference, waist-to-hip ratio, waist-to-height ratio and body fat percentage. Results: The associations between conventional anthropometric measures and abdominal fat distribution varied by ethnicity in almost all models. Europeans had the highest levels of VAT in adjusted analyses and Africans the lowest with ethnic differences most apparent at higher levels of the anthropometric measures. Similar ethnic differences were seen in the associations with SAT for a given anthropometric measure. Conclusions: Conventional anthropometric measures like BMI and waist circumference do not reflect the same amount of VAT and SAT across ethnic groups. Thus, the obesity level at which Inuit and Africans are at increased cardiometabolic risk is likely to differ from that of Europeans.